Análisis estructural comparativo entre un sistema de cimentación con monopilote y otro con grupos de cuatro pilotes, para un puente diseñado con CCP 14 - Galeano Jamauca, Alberth Yobany (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
This study presents a comparative structural analysis of two types of bridge foundations, one consisting of a group of four piles and the other consisting of a single pile, or monopile. For academic purposes of this work, information from a bridge built in Colombia, a real project, in the department of Antioquia, which has the respective geotechnical and hydrology studies required, is used. A mathematical model of the study bridge was built using CSiBridge software, which was analyzed in each of the four seismic zones defined in CCP 14, maintaining in each case the same structural configuration of the bridge. Subsequently, taking the reactions at the base of the bridge, the structural analysis and design of each type of foundation is carried out using SAP2000 software, whose output data allow comparing the variables, horizontal displacements, settlements, internal forces and quantities of materials, thus seeking to reduce the uncertainty when choosing one of the types of foundations studied, and thus providing some criteria for defining the most suitable foundation. Consequently, it is found that the monopile foundation system is adequate if used in seismic zones 1 and 2, while in zones 3 and 4, where higher earthquake loads occur, a group of 4 piles is more efficient. On the other hand, the amount of materials required for the construction of monopiles is less than that required for the foundation with groups of piles, regardless of the seismic zone where the analysis is carried out.
Keywords: Puentes-Diseños; Análisis comparativo; Cimentación-Puentes; Diseño estructural.; Bridges-Designs; Comparative analysis; Foundations-Bridges; Structural design.